The EU temporary protection directive : the directive in practice : an analysis of its implementation to protect those fleeing the war in Ukraine - Façanha, Camila Aby-Azar (2023)
The present study analyzes the European Union Temporary Protection Directive and compares it with other instruments of the Common European Asylum System. While studying the Directive, it will be examined the differences between the instruments, specifically the circumstances in which each instrument is applied and what kind of protection is granted to the individuals in each situation. Furthermore, it will use a case study to analyze and understand the actual effectiveness of the Directive. The Temporary Protection Directive was enacted for the first time by the European Commission on the 3rd of March 2022, seeking to ensure immediate protection for Ukrainian citizens and short-term nationals residing in Ukraine who had to find refuge in the European Union in the face of Russian attacks on the country. Its implementation was widely celebrated, and many individuals benefited from the instrument. However, many questions and concerns remain about the effective application of the Directive: does it offer real solutions that fill the gaps and vulnerabilities of the international regime, or does it merely seek an immediate remedy to an urgent problem? This study will analyze the practical consequences of Temporary Protection, aiming, in particular, to understand the long-term implications and consequences for those who seek and need such protection.